Comparative evaluation of the antimicrobial susceptibility and cytotoxicity of husk extract of Cocos nucifera and chlorhexidine as irrigating solutions against Enterococcus Faecalis, Prevotella Intermedia and Porphyromonas Gingivalis - An in-vitro study - Divyata Kohli; Shivayogi M Hugar; Kishore G Bhat; Parin P Shah; Madhura V Mundada; Chandrashekhar M Badakar (Wolters Kluwer Medknow Publications, 2018)
Aim and Background: The aim of the present study is to evaluate and compare the antimicrobial susceptibility and cytotoxicity of Cocos nucifera and chlorhexidine (CHX) as irrigating solutions against Enterococcus faecalis, Prevotella intermedia, and Porphyromonas gingivalis. Materials and Methods: The ethanolic extract of husk of C. nucifera was prepared. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of the extract were determined using the serial broth dilution method and its cytotoxicity was evaluated against human periodontal fibroblasts using 3-(4,5-dimethyl-thiazole-2-yl)-2,5-diphenyl tetrazolium bromide assay. Antibacterial susceptibility for two irrigating solutions, namely 2% CHX gluconate irrigant (Group I) and 1.5% C. nucifera husk irrigant (Group II), was tested against P. gingivalis, P. intermedia, and E. faecalis. Results: The MIC and MBC of C. nucifera husk extract for P. gingivalis were 468.75 μg/ml and 1562.5 μg/ml, for P. intermedia were 48.8 μg/ml and 1875 μg/ml, and for E. faecalis were 1562.5 μg/ml and 3750 μg/ml, respectively. The extract was nontoxic to the human periodontal fibroblast. Both the materials have shown similar antibacterial susceptibility and no difference was observed at baseline, 10, 30, and 60 min using two-way repeated measures of ANOVA. However, a statistically significant difference was observed between different time points for P. gingivalis and P. intermedia using Bonferroni multiple comparison test (f = 826.1390, P ≤ 0.05). Conclusion: 1.5% of ethanolic husk extract of C. nucifera has a significant antibacterial action against polymicrobial dental biofilm and its activity is comparable to that of 2% CHX which validates its use as a future irrigating solution for overcoming bacterial resistance with synthetic agents.